Religion and Public Interpretation - Gutauskas, Mintautas (Religija ir kultūra, 2010)
The article raises the question how the attitude towards religion is influenced by the changes of relation with the meaning of matters which are ascribed to religion. With reference to M. Heidegger the peculiarity of public opinion is being disclosed. The author states that secularization functions as a machinery which appropriates any meaning: the public opinion appropriates religion, reduces it to political, economical or criminal dimensions, to that of cultural heritage, so religion assumes its essence and reality in these dimensions. The author demonstrates that public interpretation functions as an unmasking machinery which strengthens that reduction and appropriation of meaning. The analysis of religion in the context of globalization shows that there is some tendency to localization of religious meaning: the religious communities tend to direct towards the radicalism and isolation.
Keywords: religion; secularization; globalization; public interpretation